JURIDICAL ANALYSIS OF DEFAULT IN MUSYARAKAH MUTANAQISAH AND IJARAH CONTRACTS (Study of Decision Number 129/Pdt.G/2023/PA.Mn) - Fiki Inayah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2026)
This study analyzes the juridical interpretation of breach of contract in Musyarakah Mutanaqisah financing through an examination of  Decision Number 129/Pdt.G/2023/PA.Mn issued by the Religious Court of Madiun. The dispute occurred between PT Bank Muamalat Indonesia Tbk and PT Hasta Mulya Putra concerning the developer’s failure to facilitate the transfer of property ownership for customers financed through Islamic home financing schemes. This research aims to identify the factors causing breach of contract and examine judicial reasoning in interpreting the relationship between developer obligations and Musyarakah Mutanaqisah contracts. This research uses normative legal research with statute and case approaches. Data were obtained through documentation techniques from court decisions, legislation, books, and scientific journals related to Islamic economic law. The findings show that breach of contract occurred due to the developer's failure to prepare Sale and Purchase Deeds (AJB) and transfer ownership certificates to customers. The judges interpreted the developer’s declaration as an integral part of the Musyarakah Mutanaqisah financing scheme, thus bringing the dispute within the jurisdiction of the Religious Court. This decision illustrates the dynamic development of Islamic economic dispute resolution and may serve as jurisprudence for similar cases in Indonesia.